Monkeys fight more in polluted air - Aichun Xu (Nature Portfolio, 2021)
Abstract Air pollution is a global environmental problem, and its effects on human behavior, psychology, and health have been well studied. However, very few studies were done on if and how air pollution affects animal behavior, for example, social conflict. Many physiological and psychological evidences suggest a possible positive relationship between air pollution and animal social conflict, thus we established a multiple linear regression model using a captive monkey group to explore if monkeys behave more aggressively in polluted air. Our results confirmed that daily social fighting behaviors occurred more when air is polluted. Temperature has a nonlinear effect on monkey social conflict, with a fighting peak at 25–29 °C. To our knowledge, this is the first report that animal social conflict, like humans, is also affected by air pollution and temperature.